The Marajoara influence in Brazilian Art Déco - Roiter, Marcio Alves (Revista UFG, 2017)
Marajó in the Brazilian Amazon, the world’s largest fluvio-marine island, had already undergone several phases of development before the arrival of the Portuguese colonizers. The Marajoara phase, considered the most significant, stretching from 400 to 1350, left behind an array of innumerable exquisitely decorated artifacts, such as funeral urns, benches, sculptures, vases, tangas and ornaments in stone, terracotta, ceramic and clay. Twentieth-century inventions, such as cars, airplanes and seaplanes, plus the adventurous spirit of many scientists, historians, journalists, businessmen, and even looters, made Marajó a very popular place to visit. Artifacts of the preCabral era were much sought after worldwide by museums, collectors and art dealers. Brazilian art tuned into this moment, and a group of creative individuals took advantage of this line of business. In fields as diverse as literature and music, architecture and the applied arts, the Nativists were born. (...)